Pengaruh Likuiditas Dan Profitabilitas Terhadap Price Earning Ratio Pada PT. Indofood Sukses Makmur Tbk. - Amelia Amelia; Tri Diana (Jurnal Ekonomi STIEP, 2019)
The research objective is to investigate and analyze the influence of current ratio and return on equity on the price earning ratio at the Indofood Sukses Makmur Tbk, either partially and simultaneously. The study used survey methods in an attempt to gather more field data assisted with research instruments adapted to the characteristics of descriptive qualitative research, in this case the researcher provides financial ratios are adjusted to the dimensions of the study variables. This research resulted that current ratio and return on equity simultaneously affected significantly to price earning ratio. While partially, only return on equity that has affected price earning ratio while current ratio not significance.